O cogito pré-reflexivo: Jean-Paul Sartre e a filosofia da mente - Veronica de Souza Campos (2018)
The twentieth century witnessed, in its final decades, a renewal of interest in the philosophy of Jean-Paul Sartre within anglophone circles. This renaissance is part of a broader movement, marked by the approach of problems regarding consciousness and the role of mind in action, which resulted in several initiatives to revisit existential phenomenology from new perspectives. One of these perspectives aims to explore Sartre's idea of pre-reflexive consciousness and the possible contributions that this idea might be capable of providing in contemporary debates on the nature of consciousness, cognition, perception and action. With this in view, this work i) presents and discusses some of the exegetical misunderstandings around the main sartrean theses regarding the conscious mind, in order to clarify them as well as to show that Sartre has been erroneously taken as an hyper-intellectualist, specially in virtue of a certain incomprehension about his idea of pre-reflexive consciousness; ii) presents and discusses two interpretative hypotheses about Sartre's notion of nonthetic consciousness, in order to make it clear the strengths and weaknesses of each one of them as well as to broaden our understanding of what exactly Sartre intended when he brought this notion into play; and iii) presents and discusses some theoretical and empirical issues that might challenge Sartre in the light of the notion in question